MANDEH BAY, WEST SUMATERA DISTRIBUTION OF OCEANOGRAPHIC PARAMETERS IN THE WATERS - Okse Tudela Indra; Musrifin Galib; Ulung Jantama Wisha (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Department of Marine Science, Faculty of Fisheries and Marine ScienceUniversity of Riau, Pekanbaru, Indonesiaoksetudela@gmail.comMandeh is filled with household activities and development that produce pollutants into the surrounding waters. This condition can cause environmental problems, and changes in water conditions. Understanding the dynamics of physical and chemical waters in Mandeh waters is very important as an effort to overcome environmental problems as part of coastal area management and protection. The purpose of this study is to understand the distribution of oceanographic parameters in Mandeh waters. Primary database (current velocity for 1 day, physical and chemical waters data taken by in situ) and secondary data (tides). The hydrodynamic simulation results are based on MIKE 21. The hydrodynamic simulation results show that the current velocity ranges from 0-1.14 m / s. The results of physical and chemical parameters were analyzed by ArcGIS 10 to determine the spatial distribution of all parameters. Surface temperatures range from 27-30 0C, acidity levels range from 6.7 to 8.3, dissolved oxygen ranges from 2.8-7 mg / l, salinity ranges from 33.1 to 33.5 ppm. The distribution of all physical and chemical parameters is influenced by current and tidal movements. Mandeh waters with point -11, according to the Storet Method are categorized as medium polluted waters.Keywords: oceanographic parameters, numerical model, Mandeh waters, water pollution1) Student of Faculty of Fisheries and Marine